2014
DOI: 10.1161/atvbaha.114.303801
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assembly of Kv7.1/Kv7.5 Channels With Emerging Properties on Vascular Muscle Physiology

Abstract: Objective— Voltage-dependent K + (Kv) channels from the Kv7 family are expressed in blood vessels and contribute to cardiovascular physiology. Although Kv7 channel blockers trigger muscle contractions, Kv7 activators act as vasorelaxants. Kv7.1 and Kv7.5 are expressed in many vessels. Kv7.1 is under intense investigation because Kv7.1 blockers fail to modulate smooth muscle reactivity. In this study, we analyzed whether Kv7.1 and Kv7.5 may form functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The simulated macroscopic current (Figure 5O) displays the two signatures of recorded macroscopic Kv7.1 ionic currents: a short initial delay (5 to 10 ms) and early inactivation. Additionally, the activation duration is consistent with that of the experimentally recorded currents (Oliveras et al, 2014; Shamgar et al, 2008; Wu et al, 2010a; Wu et al, 2010b). …”
Section: Discussionsupporting
confidence: 85%
“…The simulated macroscopic current (Figure 5O) displays the two signatures of recorded macroscopic Kv7.1 ionic currents: a short initial delay (5 to 10 ms) and early inactivation. Additionally, the activation duration is consistent with that of the experimentally recorded currents (Oliveras et al, 2014; Shamgar et al, 2008; Wu et al, 2010a; Wu et al, 2010b). …”
Section: Discussionsupporting
confidence: 85%
“…The voltage-dependence for activation varies among Kv7 channel subtypes when expressed in mammalian cells, with Kv7.5 activating at more negative voltages than other subtypes. The V 0.5 of activation of HASMC Kv7 currents (−41 mV) is most similar to that reported for cloned Kv7.5 channels expressed in mammalian cells (−44.2 ± 1.7 mV; −46 ± 3 mV [13,17]) and considerably more negative than that of Kv7.4 (−30.6 ± 1.2 mV [13]), or Kv7.3 (−37.3 ± 1.3 mV [18]). All told, the experimental evidence suggests that the endogenous Kv7 currents measured in HASMCs are elicited predominantly via Kv7.5 channels.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, it is plausible that cGMP may activate K v 7 channels through a PKA‐dependent activation of K v 7 channels (Chambard & Ashmore, ; Mani et al, ). Interestingly, we and other authors have shown that K v 7.5 may form functional heterotetrameric channels with K v 7.1 (Oliveras et al, ) and K v 7.4 (Brueggemann et al, ) in vascular tissues. Thus, it is conceivable that activation of K v 7.1/K v 7.5 or K v 7.4/K v 7.5 heterotetramers could contribute to cGMP‐mediated responses as previously proposed (Stott et al, ).…”
Section: Discussionmentioning
confidence: 53%